Higher Altitude and Risk of Bronchopulmonary Dysplasia among Preterm Infants - Lee, Shoo K.; Ye, Xiang Y.; Singhal, Nalini; De La Rue, Sarah; Lodha, Abhay; Shah, Prakesh S.; null (American Journal of Perinatology, 2013)
Objective To assess the association between altitudes of neonatal intensive care units (NICU) and the rate of bronchopulmonary dysplasia (BPD) and BPD/death in very preterm infants.Study Design Data from infants born at <33 weeks' gestation admitted to Canadian Neonatal Network during 2008 and 2009 were analyzed. The associations between the altitude of NICU and the BPD and altitude and BPD/death were determined using logistic regression models.Results Of 7551 eligible infants, 1540 (20%) were admitted to NICUs at an altitude > 400 m, 3661 (48%) between 86 and 400 m, 2350 (31%) at ≤85 m. The incidences of BPD (21.7% versus 17.2%) and BPD/death (26.2% versus 23.0%) were significantly higher in the infants admitted to NICUs at >400 m altitude versus those ≤400 m altitude (p < 0.01). In multivariable analyses, the adjusted odds ratio was 1.81 (95% confidence interval [CI] 1.05 to 3.12) for BPD and 1.79 (95% CI 1.12 to 2.85) for BPD/death among infants admitted to NICUs at altitude > 400 m compared with NICUs at altitude ≤ 400 m. For each 100-m increase in altitude, the odds increased by 8% for BPD (95% CI 4 to 13%) and 9% for BPD/death (95% CI 5 to 13%); however, the increase was mainly due to increase in BPD.Conclusion For very preterm infants, higher altitude of NICUs increased the risk of BPD.
Keywords: infant; premature; altitude; chronic lung disease; morbidity